Status of glycemic control and lipid profile in type 2 diabetes mellitus: A descriptive cross-sectional study - Koirala, Sarbottam; Piryani, Rano Mal; Shahi, Akash; Bhandari, Shristi; Shah, Sanjay (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Dyslipidemia in diabetes mellitus is commonly seen in the form of high total cholesterol (TC), high lowdensity lipoprotein (LDL), high triglyceride (TG) and low high-density lipoprotein (HDL) levels. This study was done to study the association of glycemic control with lipid profile in Type 2 Diabetes Mellitus (T2DM) patients.Methods:This was a cross sectional, observational study conducted from December 2018 to June 2020 at Universal College of Medical Sciences and Teaching Hospital, Bhairahawa. It involved 125 patients of type 2 diabetes mellitus (68 males and 57 females), who visited in outpatient department of Internal Medicine. Laboratory tests [(Fasting Blood Sugar(FBS), Post Prandial Blood Sugar (PPBS), Glycosylated Hemoglobin (HbA1c), Renal Function Test (RFT) and Fasting Lipid Profile] were noted. The data was analyzed with SPSS Version 25. Descriptive statistics like frequency, percentage,mean and standard deviation (SD) were calculated. Independent t-test was used to measure the association between glycated hemoglobin with blood glucose level and glycated hemoglobin with lipid profile.Results: The study patients were categorized into two groups on the basis of HbA1C level [(good glycemic control ≤7 (n=33) and poor glycemic control >7 (n=92)]. In good glycemic control the mean TC was 143.30, LDL 71.88, HDL 43.70, VLDL 29.55, TG 134.39 mg/dl while in poor glycemic control the mean TC was 182.47, LDL 114.85, HDL 32.03. VLDL 36.61, TG 179.33 mg/dl with p-value